O fenômeno dos blogs street-style : do flâneur ao star blogger - Hinerasky, Daniela Aline (2013)
This research investigates the street style blog phenomenon, in the narcissistic digital society, in order to comprehend it s logic and it s interlocutors, and in particular, to understand the collective imaginary of street fashion and blogger dynamics, as they are flâneurs of contemporaneity and emblematic fashion icons. Amongst the objectives aimed, the digital street style movement is explored and described from a historical and editorial structure perspective. A systematization through typology is also proposed for the street style blogs genre in this research.We have started the investigation with a study of technical aspects of blogs and the formation of styles from traits traced in modern and postmodern urbanity to better recognize these blogs not only as a strategic communication vehicles but as environments of interaction and projection spaces for individuals and social groups that target acknowledgment and fame. From a Comprehensive Sociology approach to map the street style blogging phenomenon, a quanti-qualitative research was realized, in which included a wide collection of blogs, gathering of data and netnographic observation of the corpus (The Sartorialist, The Face Hunter, Garance Dore, Easy Fashion Paris, RIOetc, My Little Fashion Diary, Art Of The Trench), during the months of May and October 2011, participant observation and a field log updated daily about the dynamics of data gathering on the bloggers and the interviews. In this process, we distinguished five types of blogs: locative street style; street style cool hunters; street style diary (or ego blogs); corporate and mixed, which are blogs that translate a cultural text about fashion, consumption and daily urban life. Street style blogs are a virtual roadway where the street represents the symbolic universe of the runways and it s surroundings. It is noteworthy that any version of a street style blog is edited, therefore, it could represent a personal, structural professional or marketer point of view. In this discussion, the street exceeds the dimensions of physical places. It s all about a relational space, the exuberance of crossing to one sidewalk to another, a laboratory of style construction, a dialogue between persons, the stage of an spectacle and the gateway to stardom for these bloggers and cultural intermediators.